2015
DOI: 10.4102/sajhrm.v13i1.675
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership as a source of optimism, trust in the organisation and work engagement in the public health care sector

Abstract: Orientation: The orientation of this study is towards authentic leadership (AL) and its influence on optimism, trust in the organisation and work engagement of employees in the public health care sector.Research purpose: The objectives of this study were to determine whether the leadership style of AL could predict optimism, trust in the organisation and work engagement amongst a large sample of employees from various functions in public hospitals and clinics in Gauteng and to establish whether optimism and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 49 publications
7
64
0
2
Order By: Relevance
“…This research theme included research on many psychological and rather personal issues involving working life. To be precise, the studies in this category included research on AL's relationship with psychological wellbeing at work (Nelson et al, 2014), work engagement (Bamford et al, 2013;Stander et al, 2015), job satisfaction (Giallonardo et al, 2010;Wong and Spence Laschinger, 2013;Spence Laschinger and Fida, 2014b;Rahimnia and Sharifirad, 2015;Read and Spence Laschinger, 2015;Spence Laschinger and Fida, 2015;, creativity (Malik et al, 2016), two dimensions of thriving (learning and vitality) (Mortier et al, 2016), voice behaviour (Wong and Cummings, 2009;Wong et al, 2010), performance (Wong and Cummings, 2009;Wong and Spence Laschinger, 2013) Part of the mediating factors in these studies were individual issues, such as personal and social identification (Wong et al, 2010;, occupational coping self-efficacy , psychological capital (Spence Laschinger and Fida, 2014b), trust in organisation (Stander et al, 2015), trust in manager (Wong and Cummings, 2009;Wong et al, 2010), person-job match (Bamford et al, 2013;Spence Laschinger and Read, 2016), optimism (Stander et al, 2015), empathy (Mortier et al, 2016), job satisfaction (Spence Laschinger et al, 2012), work engagement (Giallonardo et al, 2010;Wong et al, 2010), attachment insecurity (Rahimnia and Sharifirad, 2015), emotional exhaustion (Spence Laschinger et al, 2012; Laschinger and Fida, 2014a; Spence Laschinger and Fida, 2014b), cynicism (Spence Laschinger and Fida, 2014a; Spence Laschinger and Fida, 2014b), and burnout . Other mediating factors, such as work climate (Nelson et al, 2014), civility norms (Spence Laschinger and , patient care quality (Spence Laschinger and Fida, 2015), use ...…”
Section: Wellbeing At Workmentioning
confidence: 99%
“…This research theme included research on many psychological and rather personal issues involving working life. To be precise, the studies in this category included research on AL's relationship with psychological wellbeing at work (Nelson et al, 2014), work engagement (Bamford et al, 2013;Stander et al, 2015), job satisfaction (Giallonardo et al, 2010;Wong and Spence Laschinger, 2013;Spence Laschinger and Fida, 2014b;Rahimnia and Sharifirad, 2015;Read and Spence Laschinger, 2015;Spence Laschinger and Fida, 2015;, creativity (Malik et al, 2016), two dimensions of thriving (learning and vitality) (Mortier et al, 2016), voice behaviour (Wong and Cummings, 2009;Wong et al, 2010), performance (Wong and Cummings, 2009;Wong and Spence Laschinger, 2013) Part of the mediating factors in these studies were individual issues, such as personal and social identification (Wong et al, 2010;, occupational coping self-efficacy , psychological capital (Spence Laschinger and Fida, 2014b), trust in organisation (Stander et al, 2015), trust in manager (Wong and Cummings, 2009;Wong et al, 2010), person-job match (Bamford et al, 2013;Spence Laschinger and Read, 2016), optimism (Stander et al, 2015), empathy (Mortier et al, 2016), job satisfaction (Spence Laschinger et al, 2012), work engagement (Giallonardo et al, 2010;Wong et al, 2010), attachment insecurity (Rahimnia and Sharifirad, 2015), emotional exhaustion (Spence Laschinger et al, 2012; Laschinger and Fida, 2014a; Spence Laschinger and Fida, 2014b), cynicism (Spence Laschinger and Fida, 2014a; Spence Laschinger and Fida, 2014b), and burnout . Other mediating factors, such as work climate (Nelson et al, 2014), civility norms (Spence Laschinger and , patient care quality (Spence Laschinger and Fida, 2015), use ...…”
Section: Wellbeing At Workmentioning
confidence: 99%
“…The current study results partially agree with many of studies conducted on 2016) that showed correlations ranged from weak to moderate, and higher than transactional leadership style (Strom et al, 2014). In addition, other studies conducted on authentic leadership style showed positive significant correlation with work engagement such as Maximo (2015) and Stander et al (2015). Besides, some other studies conducted on servant leadership style showed positive significant correlation with work engagement that its strength is higher than others such as Villier (2015) and Jafai et al (2016).…”
Section: Discussion:-mentioning
confidence: 91%
“…Prior studies confirm the positive affect of authentic leadership to several posi tive work out comes such as leader-member exchange (Wang et al, 2014), work engagement (Wong et al, 2010;Stander et al, 2015), helping behavior (Hirst et al, 2016), follo wer empower ment, and identi fication with supervisor (Walum bwa et al, 2010).…”
Section: Introductionmentioning
confidence: 91%